Sistem Informasi Anggaran Pendapatan Dan Belanja Sekolah Pada Smk N 1 Kendal Dengan Metode Bottom-Up Berbasis Web - Haidar, Laksamana Rajendra Haidar; Haris Ihsanil Huda; Edy Siswanto (Pusat Riset dan Inovasi Nasional, 2022)
Currently SMK N 1 Kendal is still recording school income and expenditure budgets manually, but the more stringent accountability reporting on the use of the budget, it is necessary to have an information technology system that is efficient, useful and makes it easier for the treasurer to process and report the revenue and budget budgets. school shopping. This study aims to implement a school income and expenditure budget information system application with a web-based bottom-up method so that the process of recording school income and expenditure data is more effective. The application that will be used is developed using Macromedia Dreamweaver 8 as a coding tool and MySQL as the database. With the implementation of this school income and expenditure budget information system, errors and loss of income and expenditure data will be minimized at SMK N 1 Kendal, besides the time required to obtain the required data will be much faster and more accurate. The process of reporting receipts and expenses automatically aims to make it easier for users. In addition, the time required to complete the school income and expenditure budget report will be much shorter.